Protocol for detecting neuronal subnetworks from in vivo calcium imaging data using multiple clustering algorithms in MATLAB - Jui-Yen Huang; Gautam Chauhan; Pei-Ying Chen; Esen Tuna; Hui-Chen Lu (STAR Protocols)
Summary: Neuronal subnetworks, defined by co-activation patterns, are fundamental units of brain computation. We provide a step-by-step workflow to detect subnetworks from in vivo calcium imaging data using multiple clustering algorithms in MATLAB. We apply statistical modeling in R to evaluate group-level differences, followed by model selection and bootstrapping for robust estimation. Finally, we use an R Markdown template to generate a structured statistical report.For complete details on the use and execution of this protocol, please refer to Huang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.